Healthcare resource utilization and costs of care in the United States for patients with non-alcoholic steatohepatitis. (31st December 2023) - Tapper, Elliot B.; Bonafede, Machaon; Fishman, Jesse; Dodge, Stephen; Miller, Keith; Zeng, Ni; Lewandowski, Dave; Bogdanov, Alina
Abstract: Aims: This retrospective, observational cohort study aimed to determine the burden of comorbidities, hospitalization, and healthcare costs among patients with non-alcoholic steatohepatitis (NASH) in the United States stratified by fibrosis-4 (FIB-4) or body mass index (BMI). Methods: Adults with NASH were identified in the Veradigm Health Insights Electronic Health Record Database and linked Komodo claims data. The index date was the earliest coded NASH diagnosis between 1 January 2016 and 31 December 2020 with valid FIB-4 and ≥6 months of database activity and continuous enrollment pre- and post-index. We excluded patients with viral hepatitis, alcohol-use disorder, or alcoholic liver disease. Patients were stratified by FIB-4: FIB-4 ≤ 0.95, 0.95 < FIB-4 ≤ 2.67, 2.67 < FIB-4 ≤ 4.12, FIB-4 > 4.12) or BMI (BMI <25, 25 ≤ BMI ≤30, BMI > 30). Multivariate analysis was used to assess the relationship of FIB-4 with costs and hospitalizations. Results: Among 6, 743 qualifying patients, index FIB-4 was ≤0.95 for 2, 345 patents, 0.95–2.67 for 3, 289 patients, 2.67–4.12 for 571 patients, and >4.12 for 538 patients (mean age 55.8 years; 62.9% female). Mean age, comorbidity burden, cardiovascular disease risk, and healthcare utilization increased with increasing FIB-4. Mean ± SD annual costs increased from 16, 744±53, 810 to 34, 667±67, 691 between the lowest and highest FIB-4 cohorts and were higher among patients with BMI <25 (24, 568±81, 250) than BMI >30 (21, 542±61, 490). A one-unit increase in FIB-4 at index was associated with a 3.4% (95%CI: 1.7%–5.2%) increase in mean total annual cost and an 11.6% (95%CI: 8.0%–15.3%) increased likelihood of hospitalization. Conclusions: A higher FIB-4 was associated with increased healthcare costs and risk of hospitalization in adults with NASH; however, even patients with FIB-4 ≤ 0.95 presented a significant burden.